Formation of motives of martial arts students in pc educational psychophysical activities - Shchegolev V.A.; Sushchenko G.V.; Murinchik E.S.; Pakhodnya M.O. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to theoretically and experimentally substantiate the methodology for forming motives for psychophysical activity among student martial artists. Methods and structure of the study. The experiment was conducted on the basis of Peter the Great St. Petersburg Polytechnic University and was aimed at developing stable motives for psychophysical activity among student martial artists. Results and conclusions. To increase the effectiveness of training of martial arts athletes at a university, it is important to substantiate a system of priority areas that ensure the effective functioning of their psychophysical activity, the basis of which, first of all, is the optimal level of development of psychomotor, conditioning and coordination abilities.